Adipose-derived stem cells: a pain relief treatment for intervertebral disc degeneration - Pont, Dr Jeremy; Singh, Prof. Pankaj; Singh, Prof. Vivek Pratap (International Journal of Scientific Research and Management (IJSRM), 2025)
Intervertebral Disk Degeneration, or IVDD, refers to the natural process in which an intervertebral disk deteriorates (i.e., degenerates) over time-years and decades of life. It could result from the natural aging process or due to simple wear and tear. One of the most important components in spinal mechanics is the vertebral disc. It acts as a cushion between vertebral bodies connects them, and works as a shock-absorber during daily activities besides being the weight-bearing structure of vertebrae. IVDD is a major contributing factor to millions of lower back pain (LBP) sufferers worldwide. However, treatments to date are mostly pain-based (pain management: hitherto by surgical or non-surgical methods) and not disease-oriented due to a lack of understanding concerning the underlying mechanisms that trigger disc degeneration as reviewed in recent publications. While research has focused on reversing the degeneration process, adipose-derived stem cells (ADSCs) have shown promise as potential candidates because they are known to modulate immune responses and differentiate into multiple cell types making them an attractive prospect for regenerative therapy and a pain relief treatment. The present review article is intended to underscore the therapeutic features of ADSCs and their prospect in treating IVDD via innovative mechanisms, reviewing preclinical & clinical evidence along with future directions.